2019
DOI: 10.1111/sjop.12550
|View full text |Cite
|
Sign up to set email alerts
|

Role clarity, role conflict, and vitality at work: The role of the basic needs

Abstract: Karkkola, P., Kuittinen, M. & Hintsa, T. (2019). Role clarity, role conflict, and vitality at work: The role of the basic needs. Scandinavian Journal of Psychology, 60,[456][457][458][459][460][461][462][463] This study aimed to provide new information on the relationships between vitality at work and role clarity, role conflict, and psychological basic need satisfaction. Participants of the cross-sectional study were 110 employees in a preventive intervention program. Associations between the focal constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Finally, supervisor support, overall organizational justice, and role clarity was found to be associated with a lower likelihood of membership into the Low Empowerment profile relative to the Moderately High Empowerment and Impact profile. These results thus add further evidence to research supporting the adaptive role of supervisor support (Caesens et al, 2020), overall organizational justice (Ambrose & Schminke, 2019;Bernhard-Oettel et al, 2020), and role clarity (Karkkola et al, 2019;Whitaker et al, 2007). Despite these generally positive effects of job resources on PE, it is noteworthy that role clarity seems to have the strongest effects on PE.…”
Section: Predictors Of Pe Profilessupporting
confidence: 70%
See 1 more Smart Citation
“…Finally, supervisor support, overall organizational justice, and role clarity was found to be associated with a lower likelihood of membership into the Low Empowerment profile relative to the Moderately High Empowerment and Impact profile. These results thus add further evidence to research supporting the adaptive role of supervisor support (Caesens et al, 2020), overall organizational justice (Ambrose & Schminke, 2019;Bernhard-Oettel et al, 2020), and role clarity (Karkkola et al, 2019;Whitaker et al, 2007). Despite these generally positive effects of job resources on PE, it is noteworthy that role clarity seems to have the strongest effects on PE.…”
Section: Predictors Of Pe Profilessupporting
confidence: 70%
“…Similarly, employees who know what they need to do and what is expected of them experience choice and willingness (i.e., high levels of self-determination) because they behave in a way that is congruent with their self-endorsed values and interests (Deci et al, 2017). Finally, role clarity represents a critical job resource that is instrumental in cultivating PE (e.g., impact, competence) because it reduces job-related uncertainty (Whitaker et al, 2007), helps employees focus on essential aspects of their work (Bang et al, 2010), and allows them to effectively invest energy in their work roles (Karkkola et al, 2019).…”
Section: Predictors Of Profile Membershipmentioning
confidence: 99%
“…These aspects eventually lead to early termination or delay of CMHS [49]. A study by Karkkola et al found that role clarity through higher autonomy and higher competence can impact subjective dynamics at work [50]. Therefore, CMHWs can increase their motivation by proactively clarifying their roles and responsibilities as well as systematically learning expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Role clarity implies that the employee knows the job requirements and what is formally and informally expected of him or her. 24 According to the national guidelines, municipalities should have their own control system which should secure a clear disposition of responsibility and tasks, and where goals, tasks, and activities should be clearly defined. 2 This means that there should be a system which ensures role clarity.…”
Section: Discussionmentioning
confidence: 99%